2015
DOI: 10.1364/oe.23.002962
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond UV laser-induced fatigue effects in the bulk of synthetic fused silica: a multi-parameter study

Abstract: Multiple-pulse S-on-1 laser damage experiments were carried out in the bulk of synthetic fused silica at 355 nm and 266 nm. Two beam sizes were used for each wavelength and the pulse duration was 8 ns. The results showed a fatigue effect that is due to cumulative material modifications. The modifications have a long lifetime and the fatigue dynamics are independent of the used beam sizes but differ for the two wavelengths. Based on the fact that, in the context of material-modification induced damage, the dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
(72 reference statements)
0
6
1
Order By: Relevance
“…Multipulse irradiation to a material reportedly results in a decrease in the threshold of laser-induced damage and thus effectively produces the defects, which is known as a fatigue effect. 50 A fatigue effect arises from the cumulative material modifications by multiple laser shots. We examined the multishot effect on the defect formation by Raman analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Multipulse irradiation to a material reportedly results in a decrease in the threshold of laser-induced damage and thus effectively produces the defects, which is known as a fatigue effect. 50 A fatigue effect arises from the cumulative material modifications by multiple laser shots. We examined the multishot effect on the defect formation by Raman analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19]24) This phenomenon has been observed in synthetic silica glass and other materials in laser damage tests under UV irradiation with high photon energy. 12,16,17) It is suggested that statistical fatigue and material modification fatigue can be qualitatively distinguished by using the relationship between the number of damage pulses N D and the fluence F. 17,18) The N D (F) forms a welldefined curve in the case of material modification fatigue, whereas in the case of statistical fatigue it shows a statistically broad distribution. Although the number of measured points is relatively small, our results can be expressed as logarithmic equations [Eqs.…”
Section: ( ) ( ) ( ) = -+mentioning
confidence: 99%
“…[13][14][15] It has been discussed that the fatigue effect is caused by statistical fatigue and material modification fatigue. 12,[16][17][18][19] The rate of reduction of LIDT depends on the material and also on the mechanism of fatigue. In this study, we also evaluate the rate of reduction of the LIDT of SBO crystal under multi-shot irradiation and discuss the possible damage mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on fatigue laser damage in synthetic fused silica using UV wavelengths indicates the importance of self-focusing for the damage mechanism. 39 Similarly, one of the most complete investigations on nanosecond laser damage also includes self-focusing as the final step in their model. 34 More generally, the light-induced modifications of the material may in fact modify the propagation of the laser beam by different physical mechanisms (modification of the refractive index, thermal self-focusing, and nonlinear self-focusing) and thus cause a catastrophic enhancement of the peak fluence a bit further downstream compared to the location of the light-induced defects.…”
Section: Modification Of the Host Materialsmentioning
confidence: 99%
“…These defects have long lifetimes and accumulate pulse after pulse until the effects they have on the laser beam become sufficiently strong to cause damage. Experimental observations point toward defectinduced self-focusing of the laser beam causing damage a bit further downstream 34,39,40 rather than the defects absorbing themselves a sufficient portion of the light to induce thermal run-away and damage or the defects causing mechanical damage due to local strain in their vicinity.…”
Section: Modification Of the Host Materialsmentioning
confidence: 99%